Cardiomiopatía diabética: entidad poco conocida y el impacto terapéutico de los inhibidores del cotransportador sodio-glucosa tipo 2 en el miocardio diabetico - Solano, Jonatan Navarro (2019)
Diabetic cardiomyopathy is an entity that originates from a microvascular complication of diabetes mellitus type 2, which develops by the synergy of several metabolic elements generated by chronic hyperglycemia and oxidation of free fatty acids that cause a harmful impact by different biochemical pathways at the level of the myocardium causing structural and functional changes, as a consequence they generate diastolic and early systolic dysfunction before producing associated symptoms. Due to the above it is very important to understand this pathology from the physiopathological level, on the other hand, to establish an opportune diagnosis by established methods such as echocardiography and possible treatments at present for the improvement of myocardial contractility. In the present article we review the physiopathological mechanisms based on the metabolic processes in diabetes mellitus that affect the myocardium, generating a decrease in cardiac efficiency, thus causing a long-term heart failure, and also analyzing the most precise and conclusive diagnostic methods. to establish diabetic cardiomyopathy. On the other hand, the therapeutic effects of the inhibitory drugs of the sodium-glucose cotransporter type 2 in the myocardium will be analyzed on the basis of their benefits already proven benefits and in theories and hypotheses that have been raised from experimental and observational investigations.